On the end of evolution – Humankind and the annihilation of species - Glaubrecht, Matthias (Zoologica scripta, 2023)
For too long and with ever‐increasing ferocity during the past decades of an exponentially growing human world population, humankind has been waging a genuine war against nature, of which we ourselves are nevertheless also a part. We are plundering the unique biological treasure, the diversity of species, without which the ecosystems we rely on for our food, our water and so much more would not function. At present, we are already in the midst of a massive decline of populations and species, with a significantly higher extinction rate than the long‐term average. Driven essentially by habitat loss and degradation, direct exploitation through legal and illegal hunting and fishing as well as pesticides and pollution, within decades, 1 million species out of a total of 8 million could go extinct. Alongside climate change, this dramatic decay of biodiversity, that involves also the subsequent loss of ecosystem services, here termed ‘the end of evolution’, is another and by no means lesser threat to humanity. We can still take countermeasures, but we must transform our economy and change our way of living. As most successful strategy the protection of up to 30% of Earth's surface by 2030 was suggested, ideally based on the implementation of a consistent framework of global ecosystems, as it was agreed on by the December 2022 United Nations Conference of Parties (COP15) Montreal meeting for the Conservation on Biological Diversity.